Astrocyte reactivity after brain injury—: The role of galectins 1 and 3. Issue 12 (6th August 2015) - Sirko, Swetlana; Irmler, Martin; Gascón, Sergio; Bek, Sarah; Schneider, Sarah; Dimou, Leda; Obermann, Jara; De Souza Paiva, Daisylea; Poirier, Francoise; Beckers, Johannes; Hauck, Stefanie M.; Barde, Yves‐Alain; et al.
<x xml:space="preserve">Abstract</x> Astrocytes react to brain injury in a heterogeneous manner with only a subset resuming proliferation and acquiring stem cell properties in vitro. In order to identify novel regulators of this subset, we performed genomewide expression analysis of reactive astrocytes isolated 5 days after stab wound injury from the gray matter of adult mouse cerebral cortex. The expression pattern was compared with astrocytes from intact cortex and adult neural stem cells (NSCs) isolated from the subependymal zone (SEZ). These comparisons revealed a set of genes expressed at higher levels in both endogenous NSCs and reactive astrocytes, including two lectins—Galectins 1 and 3. These results and the pattern of Galectin expression in the lesioned brain led us to examine the functional significance of these lectins in brains of mice lacking Galectins 1 and 3. Following stab wound injury, astrocyte reactivity including glial fibrillary acidic protein expression, proliferation and neurosphere‐forming capacity were found significantly reduced in mutant animals. This phenotype could be recapitulated in vitro and was fully rescued by addition of Galectin 3, but not of Galectin 1. Thus, Galectins 1 and 3 play key roles in regulating the proliferative and NSC potential of a subset of reactive astrocytes. GLIA 2015;63:2340–2361